Penegakan Hukum Terhadap Tindak Pidana Pencurian Sepeda Motor di Semarang (Studi di Pengadilan Negeri Semarang) - Enan Andarwati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Whether by physical force or the threat of such force, stealing is always an act of coercion that involves the taking of another person's property or rights. There are factual and subjective components to theft. As a result, the author dubs his/her work "Semarang's Law Enforcement Against Criminal Acts of Theft." Recent theft incidents have raised community concern, especially since thieves' techniques have evolved. The investigation's overarching goal is to learn how the court in Decision No. 384/Pid.B/2022/PN.smg. ruled on the defendant's theft charge, taking into account the factors listed in Law No. 8 of 1981 Article 363 paragraph (1) 5th of the Criminal Code. Using a legally binding standard as the guiding principle. Specifications for descriptive analyses, and alternative data sources Decision 384/Pid.B/2022/PN.smg from the District Court of Semarang City. Article 363 paragraph (1) 5th of the Criminal Code of Law Number 8 of 1981 governs the collection of data for a literature study in the form of systematic narrative texts and direct interviews with the Legal Department of the Semarang District Court Office concerning Law Enforcement for the crime of motorbike theft.